Orientasi Pembelajaran Bahasa Arab Di Pesantren Persis (Studi Terhadap Madarasah Aliyah Persis Di Garut) - Budi, Firmansah Setia; Abdurrahman, Rizki; Suhartini, Andewi (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2025)
This study aims to explore the orientation in teaching the Arabic language at Persatuan Islam (Islamic Union) pesantren (Islamic boarding schools) around the city of Garut, West Java. This research uses a qualitative methodology, with data collection methods including observation, interviews, and documentation. The study produces several findings, the most important of which are: First, the orientation in teaching Arabic at most Persatuan Islam pesantren is religious in nature. In this context, Arabic serves as a tool rather than a goal; the objective is to understand religious texts. Second, most Persatuan Islam pesantren in Garut focus more on teaching about the Arabic language rather than teaching the language itself. Third, this approach in the Persatuan Islam pesantren does not arise in isolation but stems from their noble aim and aspiration to produce graduates with a deep understanding of religion who are beneficial to Islam and the Muslim community.